An evaluation of the serum magnesium levels in acute myocardial infarction: a hospital based cross sectional study - Chandran, M. Poorna; Kumanan, J. (International Journal of Research in Medical Sciences, 2020)
Background: Magnesium has been implicated in the pathogenesis of acute myocardial infarction and its complication like arrhythmia. Magnesium improves myocardial metabolism, inhibits calcium accumulation and myocardial cell death. Objective was to know the relationship between the serum magnesium levels and arrhythmias in patients with acute myocardial infarction. Methods: It was a hospital based cross sectional study. By using simple random method, 50 cases of acute myocardial infarction, admitted in a tertiary care hospital in Chennai for the period of two years. Simple descriptive analysis was done to find out frequencies and percentages. For the test of significance the Chi-square test was used. Results: In our study group of 50 subjects, 28 (56%) of patients developed arrhythmias and 22 (44%) of patients recovered without any complications. Variation in type of Myocardial Infarction among our study 50 patients were 22 (44%) had anterior wall MI, 21 (42%) patients had Inferior wall MI and 7 (14%) patients had anteroseptal MI. The mean Mg level for the arrhythmias patients for the day 1 and day 5 were 1.70±0.16 and 1.76±0.51 and 2.10±0.19 and for patients without arrhythmias 2.26±0.20. There is a significant difference in the magnesium levels in patients with arrhythmias and without arrhythmias. Conclusions: In acute myocardial infarct ion, patients with low magnesium levels are more prone to get arrhythmias. So magnesium treatment can be considered in patients of acute myocardial infarct ion with low magnesium levels.